Doxorubicin induces arterial stiffness: A comprehensive in vivo and ex vivo evaluation of vascular toxicity in mice. (1st August 2021) - Bosman, Matthias; Favere, Kasper; Neutel, Cédric H.G.; Jacobs, Griet; De Meyer, Guido R.Y.; Martinet, Wim; Van Craenenbroeck, Emeline M.; Guns, Pieter-Jan D.F.
Highlights: Mice were treated with doxorubicin (DOX) for two weeks (4 mg/kg/week). In vivo pulse wave velocity, a marker for arterial stiffness, was increased by DOX. Ex vivo endothelium-dependent relaxation and basal NO was decreased by DOX. Endothelial cell loss and reduced eNOS-expression was observed after DOX. In conclusion, DOX impairs endothelial function contributing to arterial stiffness. Abstract: Arterial stiffness is an important predictor of cardiovascular risk. Clinical studies have demonstrated that arterial stiffness increases in cancer patients treated with the chemotherapeutic doxorubicin (DOX). However, the mechanisms of DOX-induced arterial stiffness remain largely unknown. This study aimed to evaluate artery stiffening in DOX-treated mice using in vivo and ex vivo techniques. Male C57BL/6J mice were treated for 2 weeks with 2 mg/kg (low dose) or 4 mg/kg (high dose) of DOX weekly. Arterial stiffness was assessed in vivo with ultrasound imaging (abdominal aorta pulse wave velocity (aaPWV)) and applanation tonometry (carotid-femoral PWV) combined with ex vivo vascular stiffness and reactivity evaluation. The high dose increased aaPWV, while cfPWV did not reach statistical significance. Phenylephrine (PE)-contracted aortic segments showed a higher Peterson's modulus (Ep) in the high dose group, while Ep did not differ when vascular smooth muscle cells (VSMCs) were relaxed by a NO donor (DEANO). In addition, aortic rings of DOX-treated mice showed increased PE contraction, decreased basal nitric oxide (NO) index and impaired acetylcholine-induced endothelium-dependent relaxation. DOX treatment contributed to endothelial cell loss and reduced endothelial nitric oxide synthase (eNOS) expression in the aorta. In conclusion, we have replicated DOX-induced arterial stiffness in a murine model and this aortic stiffness is driven by impaired endothelial function, contributing to increased vascular tone.